2004
DOI: 10.1081/ese-200026329
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination Assessment of the Surroundings of the ex-Šibenik's Ferro-manganese Smelter, Croatia

Abstract: The objective of this study was chemical and radiological characterization of soil samples affected by the dust emission and slag dumping from ferro-manganese smelter as well as uptake of metals by vegetation growing on that soil. Iron was the main component of metallurgical slag deposited near the smelter. Slag material was highly enriched in Zn, Cr, Cu, Co, and Pb. V and Cr were enriched in the soil taken near the smelter approximately by a factor of two, Pb and Cu were increased fivefold whereas the mean co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…due to leaching) should decrease it. Using rubidium (Rb) as the reference element and subsoil samples as reference material, Orescanin et al (2004) found that enrichment factors of contaminant elements were high in the vicinity of a ferromanganese smelter and much lower further away. Similar results were obtained by García et al (2004) using Al as the reference element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…due to leaching) should decrease it. Using rubidium (Rb) as the reference element and subsoil samples as reference material, Orescanin et al (2004) found that enrichment factors of contaminant elements were high in the vicinity of a ferromanganese smelter and much lower further away. Similar results were obtained by García et al (2004) using Al as the reference element.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the types of ores or scrap metals processed, also iron smelters can lead to extensive contamination of surrounding soils with toxic trace elements (Garmash, 1985;Zanini et al, 1992;Orescanin et al, 2004). Usually, however, trace metal emissions will be lesser from ferrous than from non-ferrous metallurgical plants.…”
Section: Introductionmentioning
confidence: 97%
“…The concentrations of Cr, Mn, Fe, Cu, Zn, Co and Pb in bulk samples were determined by the energy dispersive Xray fluorescence (EDXRF) method [2]. Approximately 2 g of the powdered sample was pressed into a pellet (thick target) and irradiated for 7000 s. All targets were analyzed by EDXRF.…”
Section: Edxrf Analysesmentioning
confidence: 99%
“…In the past few decades, due to lack of environmental protection technology to address the dust and waste produced in the iron and steel smelting process, the Cu content in the surrounding soil was 5 times higher than background value (Orescanin et al, 2004). The study of heavy metal content in soil near a steel plant in Serbia showed that concentrations of Cd, Cu, Ni, Pb and Zn were higher than reported in European soils and higher than world average (Dragović et al, 2014).…”
Section: 4source Apportionment Of Heavy Metals In Soilmentioning
confidence: 96%